Capitalism and Corporate in Lampung Local Politics - Kurniawan, Robi Cahyadi; Hermawan, Dedy; Indrajat, Himawan; Kurniawan, Budi (KOMUNITAS: International Journal of Indonesian Society and Culture, 2019)
State and company / corporation in the context of governance are two of the three fundamental pillars of democratic development in addition to the market .Ã‚Â The relation of both, in the context of Lampung's local politics is object to study, in particular the company /SGC.Ã‚Â This research was conducted in May 2014. The study used a qualitative research type, whichÃ‚Â saw most of the intrinsic social life, with in-depth interviews with personalities and selected informants.Ã‚Â The approach used in this study is the approach of critical social science (CSS), which saw social science as a process of critical inquiry phenomenon.Ã‚Â The results showed that in Lampung local election at 2014 ago, there were strong relations between theÃ‚Â corporationÃ‚Â / company in the case of the Sugar Group Company (SGC) in the Lampung Governor Ã‚Â candidates.Ã‚Â SGC is serving as a source of funding for the campaign of the election for the last governor election in 2014. SGC does it as a way of business development.Ã‚Â